MAKING MEDIA INFORMATION IN INDONESIA PROVINCIAL HOUSE TRADITIONAL USING MACROMEDIA FLASH MX 8.0 - Ari Setianto; Fitri Sjafrina, SKom.,MMSI Fitri Sjafrina, SKom.,MMSI (Jurnal Sistem Informasi, 2009)
The development of increasingly advanced computer make the computer not only canbe used as a means of data but can also be used as a means of multimediainformation. Therefore, the writer tries to make application program that can be usedas a means of information media.In today's modern era, might have been a lot of people will have forgotten their owncustom nations, from the tribe, language, dance and house Traditional forms ofdiversity and social life. Indonesia has a variety of unique custom homes from othercountries, therefore this paper will explain about the traditional houses in IndonesiaAuthors in the scientific literature is only limited to the making of the application andmaking sketches of objects that will be used later.The application also for the information media that contain information about thetraditional houses.Through this work the author uses Macromedia Flash MX 8.0 Application to displaya form of traditional houses in the Indonesian province in order to facilitate people infinding out about the traditional houses in Indonesia.